Application of Chlorella sp. and Scenedesmus sp. in the Bioconversion of Urban Leachates into Industrially Relevant Metabolites (2022)
: This paper explores the ability of Chlorella sp. and Scenedesmus sp. to convert landfill leachates into usable metabolites. Different concentrations (0.5, 1, 5, and 10% v/v) of leachate coupled with an inorganic carbon source (Na2CO3 , and NaHCO3 ) were tested to improve biomass production, metabolites synthesis, and removal of NO3 and PO4 . The result shows that both strains can effectively grow in media with up to 5% (v/v) leachate, while significantly reducing the concentrations of NO3 , and PO4 (80 and 50%, respectively). The addition of NaHCO3 as a carbon source improved the final concentration of biomass, lipids, carbohydrates, and the removal of NO3 and PO4 in both strains.